2008
DOI: 10.1002/hep.22518
|View full text |Cite
|
Sign up to set email alerts
|

Is there a meaningful serum hepatitis B virus DNA cutoff level for therapeutic decisions in hepatitis B e antigen-negative chronic hepatitis B virus infection?

Abstract: The diagnosis of hepatitis B e antigen (HBeAg)-negative chronic hepatitis B indicating therapeutic intervention currently requires serum hepatitis B virus (HBV) DNA >2,000 IU/mL. We evaluated the severity of liver histology and the presence of histological indication for treatment in patients with HBeAg-negative chronic HBV infection focusing on those with low viremia and/or normal alanine aminotransferase (ALT). In total, 399 patients with increased ALT and detectable serum HBV DNA (chronic hepatitis B patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
150
2
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(172 citation statements)
references
References 33 publications
12
150
2
6
Order By: Relevance
“…Kumar et al [19] from India showed that more than 50% of their 1387 incidentallydetected chronic HBV carriers had evidence of progressive liver diseases for which treatment was indicated. A similar outcome has also been reported from Pakistan, Egypt and other countries [20][21][22][23][24][25] . There are studies from Bangladesh, India, South Korea and Turkey suggesting that HBeAg negative CHB patients as a whole tend to develop more significant liver fibrosis than those who are HBeAg positive [26][27][28][29][30] .…”
Section: Discussionsupporting
confidence: 87%
“…Kumar et al [19] from India showed that more than 50% of their 1387 incidentallydetected chronic HBV carriers had evidence of progressive liver diseases for which treatment was indicated. A similar outcome has also been reported from Pakistan, Egypt and other countries [20][21][22][23][24][25] . There are studies from Bangladesh, India, South Korea and Turkey suggesting that HBeAg negative CHB patients as a whole tend to develop more significant liver fibrosis than those who are HBeAg positive [26][27][28][29][30] .…”
Section: Discussionsupporting
confidence: 87%
“…It is well accepted that high HBV DNA levels play an adverse role in liver histological grading. For HBeAg-negative CHB, an HBV DNA load higher than 20,000 IU/ml or 1 ϫ 10 5 cp/ml is a common criterion for safety diagnosis; however, the finding of low HBV DNA load could not exclude the possibility of active hepatic necroinflammation (28). A previous study could not explain why significant necroinflammation existed in HBeAg-negative CHB patients with low HBV viral loads.…”
Section: Discussionmentioning
confidence: 93%
“…Measurement of HBV DNA levels is now a useful test for evaluating HBV replication and is considered a marker to determine not only the start and the endpoint of antiviral treatment but also the risk of HCC development (23,28). The clinical significance of reappearance of intrahepatic HBcAg in the reactivation phase of CHB based on HBV viral loads had not been well evaluated.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Another eight studies did not report detailed histological findings of study patients and were also excluded, [27][28][29][30][31][32][33][34] and another three studies were eliminated due to small study sizes (N < 30 patients). [35][36][37] One other study was excluded because it also included patients infected with hepatitis C virus, 38 and another study was excluded as it involved patients with significant alcohol use.…”
Section: Study Search Resultsmentioning
confidence: 99%